2021
DOI: 10.3390/su13084313
|View full text |Cite
|
Sign up to set email alerts
|

Complementarities between Operations and Occupational Health and Safety in Garments

Abstract: There is an ongoing debate in the extant literature regarding whether the relationship between occupational health and safety (OHS) and operational practices is contradictory or complementary. However, previous research has focused on companies situated in developed and highly industrialized countries. We contribute to the debate by investigating the relationship between OHS and operational practices in 50 selected garment factories in the context of a developing country (Bangladesh). We investigated OHS and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(90 reference statements)
1
3
0
Order By: Relevance
“…The findings of this study are partially aligned with the previous studies of [4,6,11,12,[22][23][24][25]. However, no previous scientific research investigated the buyers' and suppliers' roles in ergonomics, particularly in cross-border buyer and supplier contexts.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of this study are partially aligned with the previous studies of [4,6,11,12,[22][23][24][25]. However, no previous scientific research investigated the buyers' and suppliers' roles in ergonomics, particularly in cross-border buyer and supplier contexts.…”
Section: Discussionsupporting
confidence: 88%
“…Both the theme and the specific findings are critical to address employee voice at workplace. Since global buyers increasingly rely on lean for promoting productivity and OHS improvement among suppliers from developing countries (Hasle and Vang, 2021); wrongly implemented lean often leads to severe burdens for the employees (Maalouf et al , 2021; Hoque et al , 2020; Vang et al ., 2021). We found that employees' in-role and extra-role voice perceptions influenced their inclination to speak up, whereby, in general, those who internalized an inrole perception spoke up more.…”
Section: Discussionmentioning
confidence: 99%
“…Kavouras, Vardopoulos, Mitoula, Zorpas, and Kaldis (2022) posited that an accident, in its most often used definition, is defined as "any unplanned event that resulted in injury or ill health of people, or damage or loss to property, plant, materials or the environment or a loss of business opportunity" (Maalouf, Hasle, Vang, & Hamja, 2021). Historically, in the early days, work-related accidents have been regarded as a natural aspect of life.…”
Section: Employee Health and Safetymentioning
confidence: 99%